2013
DOI: 10.1371/journal.pone.0057950
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Infection with Chlamydia abortus Induces Dose-Dependent Latency and Abortion in Sheep

Abstract: BackgroundLatency is a key feature of the animal pathogen Chlamydia abortus, where infection remains inapparent in the non-pregnant animal and only becomes evident during a subsequent pregnancy. Often the first sign that an animal is infected is abortion occurring late in gestation. Despite this, little is understood of the underlying mechanisms that control latency or the recrudescence of infection that occurs during subsequent pregnancy. The aim of this study was to develop an experimental model of latency b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
75
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 32 publications
9
75
1
Order By: Relevance
“…No amplification was obtained with sample 1088D that was negative for both C. abortus and C. psittaci according to our collaborator gold standard (Longbottom et al, 2013). In contrast, we obtained amplification with PCR1, but not with PCR2, revealing the presence of C. abortus DNA in samples 1086D, 1092D, 723P and 572P.…”
Section: Performance Of the Duplex Rt-pcrmentioning
confidence: 57%
See 1 more Smart Citation
“…No amplification was obtained with sample 1088D that was negative for both C. abortus and C. psittaci according to our collaborator gold standard (Longbottom et al, 2013). In contrast, we obtained amplification with PCR1, but not with PCR2, revealing the presence of C. abortus DNA in samples 1086D, 1092D, 723P and 572P.…”
Section: Performance Of the Duplex Rt-pcrmentioning
confidence: 57%
“…The sample corresponding to a bird spleen positive for C. psittaci (case study 2) was also identified as C. psittaci with our new duplex PCR. The 27 ovine placental samples positive for C. abortus (Longbottom et al, 2013) were all correctly identified by our duplex PCR.…”
Section: Performance Of the Duplex Rt-pcrmentioning
confidence: 82%
“…The human and animal serum samples used in this study were taken from already existing serum collections of previous studies (4,5,7,10,13,14). Human serum samples were anonymized, and their use was approved by the local ethics committee of the University of Ulm (96/09) and the local ethics committee of the University Hospital Jena (2525-04/09).…”
Section: Methodsmentioning
confidence: 99%
“…(i) Experimentally infected sheep. Serum samples were obtained from three different groups of experimentally infected sheep as described in a previously published experimental model of latency (7). In that study, animals received different intranasally administered doses of infectious C. abortus elementary bodies (EBs) 8 weeks before mating and were monitored and bled over several months during pregnancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation